Exogenous ascorbate improves antioxidant defense system and induces salinity tolerance in soybean seedlings - Dehghan, Gholamreza; Rezazadeh, Leyla; Habibi, Ghader (Acta Biologica Szegediensis, 2011)
Germination, growth and antioxidant defense system were investigated under salinity stress and pre-treatment with ascorbate (ASC) in two soybean cultivars SAHAR and DPX. Sterilized seeds were soaked in distilled water or ASC solution (0, 400 mg L-1) for 4 hrs before they were sown in distilled water or NaCl solution (0, 12.5 and 50 mM). Salt stress reduced the growth of both cultivars through reduction in percentage of germination, shoot and root length and dry weight of seedling. ASC induced enhancement in growth of salt-stressed plants coupled with an increase in catalase and peroxidase activity in seedlings only in SAHAR cultivar, and an increase in superoxide dismutase activity in both cultivars. These findings led us to conclude that applied ASC counteracts the adverse effects of salt stress on growth of soybean; however, these effects were cultivar specific.